PP11 Using the "4Ps" Marketing Approach to Evaluate Health-Promoting Food Policies. A Rapid Scoping Review. (10th September 2013) - Orton, L C; Lloyd-Williams, F; Bromley, H; Hawkes, C; Taylor-Robinson, D C; O'Flaherty, M; Moonan, M; Rayner, M; Capewell, S
Abstract : Background: Population-wide policy actions to promote a healthy diet offer potentially large benefits in terms of reducing the non-communicable disease burden. However, there are wide ranges of potential options, with varying effectiveness. In order to make sense of this diversity, we conducted a rapid scoping review and tested a simple conceptual framework for categorising policies based on the marketing "4Ps" approach (Price, Product, Place and Promotion). Methods: We searched six electronic databases for quantitative assessments of the effectiveness of policies to improve people's healthy eating; to change awareness, knowledge or attitudes towards healthy eating; or to improve self-efficacy, skill or competency concerning these behaviours. Reference lists were screened, and key informants identified additional evidence. Items were systematically assessed for inclusion. We initially sought systematic reviews, followed by primary studies and modelling studies. Extracted data were categorised using the marketing 4Ps framework. Combinations of interventions were categorised as "multi-component". Included studies were synthesised as a narrative review (being too heterogeneous to combine quantitatively). Results: Price interventions are potentially powerful, with greater effects likely in vulnerable (low income) groups who are generally more price sensitive (1 systematic review; 3 econometric modelling studies). Product interventions mostly aim to reformulate products to reduce salt, fat or sugar content. There is some evidence for their effectiveness, however, formal evaluations are few (2 primary evaluations; 2 modelling studies). Promotion interventions suggest modest benefits for national media campaigns (such as "5 a day"), but more limited benefits for health education, food labelling, marketing or dietary advice (4 systematic reviews; 4 primary evaluations; 1 modelling study). Place interventions targeting food product availability have shown some success in schools and workplace settings (5 systematic reviews; 10 primary evaluations). However, more research is needed into community and neighbourhood interventions. Overall, the evidence is most convincing for comprehensive and multi-component interventions, notably those targeted at decreasing salt and trans fats consumption or increasing fruit and vegetable consumption (5 systematic reviews; 7 primary studies). Empirical and modelling evidence, across the 4Ps, supports the logical assumption that interventions are more effective when reinforced by mandatory rather than voluntary regulation. Conclusion: The marketing 4Ps framework offers a potentially useful approach for categorising the effectiveness evidence spanning a very wide range of healthy food policies. It helps identify promising interventions (such as taxes/subsidies and multi-component school/workplace interventions) as well as areas where further evidence is required (for example, on how to modify food availability in the community).